Maintenance layers for railway infrastructure in Poland - Smoczyński, Piotr; Gill, Adrian; Kadziński, Adam (Transport, 2020)
The railway network in Poland with over 19000 km is one of the biggest in the European Union (EU). At the same time safety indicators collected by the European Union Agency for Railways (ERA) show that it is one of the least safe in Europe. Consequently, all the actions taken in safety management of Polish Railways are particularly important for the society. In 2015, there was a change in the main infrastructure manager’s rulebook on track maintenance. A new process rule was introduced to replace a large set of long-established action rules. However, supervision reports of the Polish National Safety Authority indicate that the new rule is not used properly. Therefore, the current process of taking maintenance decisions on Polish Railways was described and a novel concept of maintenance layers and Maintenance Board meetings was proposed. The change would allow to choose the order of maintenance activities in a more objective way than it is done nowadays, without the necessity to make any major investments.First published online 19 January 2021